Video-Based Information Mediating Opportunities for Professional Development: A Research Intervention with Teaching-Focused Lecturers in Higher Education - Philip Moffitt; Brett Bligh (Information)
This paper contributes to the growing international interest in using video-based information in education, training, and professional development. It describes an empirical study in which we analyse the use of video-based information as educational practitioners negotiate, design, and enact their own professional development. In our study, participants are teaching-focused lecturers in engineering higher education. We describe a research intervention using the Change Laboratory methodology, with expansive learning, where video-based information is embroiled throughout. Our analyses show that video acts at various epistemic levels, from using video-based information to support claims to truth to using video-based information to provoke social negotiations of the partiality of knowledge. We examine how video-based information acts as a mediating technology for imagining, negotiating, and reflexively implementing professional developmental intentions. Our core argument is that practitioners can benefit from understanding how video-based information can mediate their own professional development in relational ways. We make three substantive contributions to scholarship: evincing a need for the prioritisation of understanding diverse epistemic functions of video-based information, advancing understanding of the role of video in theoretically informed social negotiation, and exemplifying methodological arrangements that move video-based information beyond visual representation.